The Impact of Health Education on High-Risk Pregnant Women's Knowledge of Preventing Pregnancy Complications in the Bukit Mulya Community Health Center Mukomuko Regency 2025 - Dewi Suparti; Nimas Ayu Lestari; Bella Anarkie (Universitas Dehasen Bengkulu, 2026)
In 2020, an estimated 287,000 maternal deaths occurred, equivalent to one death every two minutes. A recent WHO study reported that hemorrhage, most often occurring during or after childbirth, was responsible for nearly a third (27%) of maternal deaths, with preeclampsia and other hypertensive disorders contributing an additional 16%. The purpose of this study was to determine the effect of health education on the knowledge of high-risk pregnant women regarding the prevention of pregnancy complications in the Bukit Mulya Community Health Center (Puskesmas) working area in Mukomuko Regency. This study used a quasi-experimental